SISTEM INFORMASI MANAJEMEN ASSET BERBASIS WEB ( STUDI KASUS : PT. KRAKATAU IT CILEGON ) - Roy Amrullah; Anita Megayanti; Afrasim Yusta (Teknik Informatika Fakultas Ilmu Komputer, 2020)
Asset management is an asset management in a certain period of time that provides assurance about the value of an asset in currency units and also regulates the minimum amount of expenditure. Because the asset itself contains value and means to the agency, it must be properly managed. PT. Krakatau IT has several divisions, one of which is the Infrastructure division where there are several parts, one of which is the EUD (End User Device) unit which is in charge of maintaining, installing, repairing and changing assets. Activities carried out by the EUD unit of PT. In managing these assets, Krakatau IT still uses conventional methods, namely the process of first making the asset handover form and stored in a filing cabinet so that asset data can be lost or damaged. Asset data processing with conventional methods can make it difficult to produce reports so that the process of searching and recapitulating data takes a long time which results in ineffective and efficient presentation of a report. On this occasion the authors propose to make an information system design application to manage assets in order to be able to present information more effectively and efficiently.